The Dream in Islam: From Qur'anic Tradition to Jihadist Inspiration - Iain R. Edgar (Berghahn Books, 2011)
Edgarâ€™s timely and creative contribution to the study of dreams among Muslims and possible Islamic foundations is important for a number of reasons. Not least of which is the fact that talking about dreams is a way of communicating things about the world around dreaming. There are individual approaches to dream interpretation, and one must be cautious subscribing to an overly prescriptive and simplistic understanding of what dreams â€œmeanâ€ in any given context, nevertheless, there are broad cultural patterns in which those individual idiosyncrasies exist. Edgarâ€™s concentration on dreams places him in a fairly unique position in the world. He is fl uent, on the one hand, in the major dream theories in Western philosophy and psychotherapy, and on the other he is open minded and curious enough to explore radically different approaches to the same subject matter in the Muslim world. The subsequent body of work is, to my knowledge, unparalleled in the social sciences or humanities today. I can think of few comparable studies that bring the same high level of scholarship to the study of what may be one of the single most signifi - cant elephants in the room, when it comes to trying to understand how millions of people in the Muslim world engage with their dreams and by extension, with their daily lives. The following cases should illustrate the extent to which Pakistani Muslims may be powerfully motivated by dream narratives and dream experiences. They are both drawn from fi eld research conducted in a rural village in northern Punjab, throughout 1998 and 1999. In both cases, it was clear that the Pakistani informants assumed that dream narratives about God, the Prophet Muhammed, and the Qurâ€™an should be trusted as a faithful account of the dream experience. As must be abundantly clear in a Western European context, such assumptions are far from universal and speak both to the effectiveness of dream narratives among Pakistani Muslims as well as their very great potential for exploitation by those people who are not averse to lying about even the most sacred subjects.